2007
DOI: 10.1007/s11103-007-9139-x
|View full text |Cite
|
Sign up to set email alerts
|

Promoter analysis and immunolocalisation show that puroindoline genes are exclusively expressed in starchy endosperm cells of wheat grain

Abstract: The purolindolines are small cysteine-rich proteins which are present in the grain of wheat. They have a major impact on the utilisation of the grain as they are the major determinants of grain texture, which affects both milling and baking properties. Bread and durum wheats were transformed with constructs comprising the promoter regions of the Puroindoline a (Pina) and Puroindoline b (Pinb) genes fused to the uidA (GUS) reporter gene. Nine lines showing 3:1 segregation for the transgene and comprising all tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…Maize (Galuszka et al, 2005) Aleurone Arabinoxylan Wheat (Beaugrand et al, 2005;Beaugrand, Reis, et al, 2004;Guillon et al, 2004;Lovegrove et al, 2013;Philippe et al, 2006;Philippe et al, 2007;Robert et al, 2011;Suliman et al, 2013); oat, rye ; barley Xylan Wheat (Lovegrove et al, 2013) Xyloglucan Barley (13),(14)--D-glucan Wheat Philippe et al, 2006;Robert et al, 2011;; barley Callose Wheat (Philippe et al, 2006); barley (Wilson et al, 2012) Mannan Barley Ferulic acid Wheat (Philippe et al, 2007;Robert et al, 2011) p-Coumaric acid Wheat Tranquet et al, 2009) Xylanase Wheat (Beaugrand, Cronier, et al, 2004;Beaugrand et al, 2005;Beaugrand, Reis, et al, 2004) Glycosyltransferase Wheat (Suliman et al, 2013) Oxalate oxidase Wheat ( Wheat (Van Herpen et al, 2008;Wiley et al, 2007) Oleosin / Caleosin Rice (Chen et al, 2012); oat (Heneen et al, 2008) Puroindolines Wheat (Capparelli et al, 2005) Transfer cells Arabinoxylan Wheat Lovegrove et al, 2013;Robert et al, 2011); oat, rye, barley …”
Section: Cytokinin Dehydrogenasementioning
confidence: 99%
See 2 more Smart Citations
“…Maize (Galuszka et al, 2005) Aleurone Arabinoxylan Wheat (Beaugrand et al, 2005;Beaugrand, Reis, et al, 2004;Guillon et al, 2004;Lovegrove et al, 2013;Philippe et al, 2006;Philippe et al, 2007;Robert et al, 2011;Suliman et al, 2013); oat, rye ; barley Xylan Wheat (Lovegrove et al, 2013) Xyloglucan Barley (13),(14)--D-glucan Wheat Philippe et al, 2006;Robert et al, 2011;; barley Callose Wheat (Philippe et al, 2006); barley (Wilson et al, 2012) Mannan Barley Ferulic acid Wheat (Philippe et al, 2007;Robert et al, 2011) p-Coumaric acid Wheat Tranquet et al, 2009) Xylanase Wheat (Beaugrand, Cronier, et al, 2004;Beaugrand et al, 2005;Beaugrand, Reis, et al, 2004) Glycosyltransferase Wheat (Suliman et al, 2013) Oxalate oxidase Wheat ( Wheat (Van Herpen et al, 2008;Wiley et al, 2007) Oleosin / Caleosin Rice (Chen et al, 2012); oat (Heneen et al, 2008) Puroindolines Wheat (Capparelli et al, 2005) Transfer cells Arabinoxylan Wheat Lovegrove et al, 2013;Robert et al, 2011); oat, rye, barley …”
Section: Cytokinin Dehydrogenasementioning
confidence: 99%
“…In addition to immunogold and immunofluorescence labeling, several studies have been carried out using peroxidase-or alkaline phosphatase-linked detection systems (Chen, Chyan, Jiang, Chen, & Tzen, 2012;Wiley, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several endosperm-specific expression promoters have been isolated and analyzed from rice (Rasmussen and Donaldson, 2006), wheat (Wiley et al, 2007), maize (Russell and Fromm, 1997), and barley (Choi et al, 2003). However, few promoters with endosperm-specific expression have been examined in plant genetic transformation studies, as the transgenic plants showed unsatisfactory expression levels and patterns (Li et al, 2008;Qu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular genetic studies of the friabilin genes in different types of wheat have suggested that PINA is a major contributor of grain softness (Chen et al 2006;Giroux et al 2000), and functions with PINB (Amoroso et al 2004). Puroindoline genes are expressed in starchy endosperm cells, and their products are developmentally accumulated in the endosperm (Digeon et al 1999;Turnbull et al 2003a;Wiley et al 2007). PINA and PINB proteins are co-localized to the starch granule surface in the wheat endosperm, possibly due to the association of positively charged friabilins with polar lipids on the surface of starch (Feiz et al 2009).…”
mentioning
confidence: 99%